2018
DOI: 10.1083/jcb.201804048
|View full text |Cite
|
Sign up to set email alerts
|

Occluding junctions as novel regulators of tissue mechanics during wound repair

Abstract: In epithelial tissues, cells tightly connect to each other through cell-cell junctions, but they also present the remarkable capacity of reorganizing themselves without compromising tissue integrity. Upon injury, simple epithelia efficiently resolve small lesions through the action of actin cytoskeleton contractile structures at the wound edge and cellular rearrangements. However, the underlying mechanisms and how they cooperate are still poorly understood. In this study, we combine live imaging and theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Finally, SJs regulate the mechanical properties of the embryonic epidermis [8]. On the other hand, we show that Nrx-IV loss of function does not seem to affect AJ localization, which is also supported by previous studies [16] [17] [18] [8].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, SJs regulate the mechanical properties of the embryonic epidermis [8]. On the other hand, we show that Nrx-IV loss of function does not seem to affect AJ localization, which is also supported by previous studies [16] [17] [18] [8].…”
Section: Resultssupporting
confidence: 91%
“…Namely, it has been shown that Nrx-IV, together with other SJ molecules (Yurt, Coracle, and the Na + /K + -ATPase), acts to maintain apical-basal polarity during early embryonic stages, before the SJ barrier function is established, but not during late embryogenesis, when the SJ barrier function is fully established [14]. Other SJ proteins have also been shown to regulate cell shape and rearrangements during salivary gland formation and wound closure [15] [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Live imaging was performed as described previously (Carvalho et al, 2018). Dechorionated stage 15 embryos were mounted on their ventral side on glass-bottomed culture dishes (MatTek) with embryo glue (double-sided tape diluted in heptane) and covered with halocarbon oil 27 (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Wound healing in simple epithelia is characterized by the accumulation of F-actin and Non-muscle Myosin II (Myosin) at the cell boundaries that face the wound, forming an actomyosin cable that contracts and brings cells together, thereby closing the wound (Bement et al, 1999; Danjo and Gipson, 1998; Kiehart et al, 2000; Xu and Chisholm, 2011). Additionally, wound healing involves cell crawling mediated by actin protrusions (Abreu-Blanco et al, 2012; Verboon and Parkhurst, 2015) and cellular rearrangements (Carvalho et al, 2018; Razzell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%